Reproductive tract development and puberty in two lines of Nellore heifers selected for postweaning weight - Monteiro, F. M. [UNESP] (2013)
The objective was to evaluate reproductive tract development (ovary and uterus) and onset of puberty in two lines of Nellore heifers (Bos indicus) selected for postweaning weight. A total of 123 heifers, including 46 from the control Nellore line (NeC) and 77 from the selection Nellore line (NeS) were used. Every 18 to 21 days from 12 to 24 months of age, average ovarian area (OVA), endometrial thickness (ETh), and diameter of the largest follicle in each ovary were evaluated (using transrectal ultrasonography), and body weight, hip height, and body condition score were measured. There were no differences between NeS and NeC heifers for ETh or OVA (P < 0.05). Genetic selection for higher postweaning weight had no negative influence on the onset of puberty, with 52% and 48% of NeC and NeS heifers, respectively, pubertal at 24 months of age (P = 0.49). Heifers that reached puberty at the end of the study were heavier (NeC, 296.9 vs. 276.7 kg; NeS, 343.5 vs. 327.9 kg; P < 0.01) and younger (NeC, 23.4 vs. 24.2 mo; NeS, 22.7 vs. 24.0 months; P < 0.01) than those that did not. Furthermore, heifers that were heavier at weaning reached puberty earlier. Pubertal heifers had a greater OVA (4.15 vs. 3.14 cm2; P < 0.01) and ETh (12.15 vs. 9.93 mm; P < 0.01) than nonpubertal heifers. Taken together, OVA and ETh had positive effects (P < 0.01) on the onset of puberty and were suitable indicator traits of heifer sexual precocity in pasture management systems. However, selection for weight did not alter ovarian or endometrial development, or manifestation of puberty at 24 months of age. Among the growth traits studied, weaning weight and weight at puberty had significant positive effects on manifestation of first estrus. © 2013 Elsevier Inc.